2021
DOI: 10.22363/2313-0245-2021-25-3-202-208
|View full text |Cite
|
Sign up to set email alerts
|

Nursing awareness of oxygen therapy among nurses at selected district hospital in Nepal

Abstract: Relevance . Oxygen therapy is commonly used in the emergency and critical cases which is the first line treatment in many critical conditions. Oxygen therapy is a medical treatment prescribed mainly for hypoxic patients, which provides oxygen at higher concentrations than that found in atmosphere (21%). Oxygen administering depends on the needs of the patients conditions and in some cases medical treatment. The present study aims to assess the level of awareness on oxygen therapy among nurses and examine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Multiple studies from Ethiopia found average levels of OT knowledge and practice among hospital‐based nurses, 24–27 while studies from Iraq reported extremely low knowledge and practice scores among nurses 28,29 . Low knowledge and OT practice were also measured among nurses in Sudan, 30 Turkey, 31 Nepal 32 and Iran 33 . A KAP study from Nigeria found significantly higher OT knowledge among doctors (60.7%) than nurses (29.7%); however, OT practice scores were low for both doctor and nurse participants 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies from Ethiopia found average levels of OT knowledge and practice among hospital‐based nurses, 24–27 while studies from Iraq reported extremely low knowledge and practice scores among nurses 28,29 . Low knowledge and OT practice were also measured among nurses in Sudan, 30 Turkey, 31 Nepal 32 and Iran 33 . A KAP study from Nigeria found significantly higher OT knowledge among doctors (60.7%) than nurses (29.7%); however, OT practice scores were low for both doctor and nurse participants 34 .…”
Section: Introductionmentioning
confidence: 99%